The Relationship between Job Crafting and Turnover Intention: The Mediating Role of Job Satisfaction and Organizational Commitment in the Private Sector Organizations in Riyadh - Nassani, Abdelmohsen A.; Alassadi, Haneen T.; Alhussan, Majd M. (The Arab Journal of Administration, 2025)
The objective of the study aims to examine whether job crafting, job satisfaction, commitment, and turnover behavior are related. The study was applied to the private sector employees at Al Riyadh, Saudi Arabia. The research samples involved 216 respondents, and the data was gathered via an online questionnaire and statistically analyzed using SPSS and Amos, where SPSS mainly used for statistical methods such as (standard deviation, mean, reliability analysis, and correlation analysis) and for AMOS (conformity factor analysis and path analysis). The study results clearly show that: (1) there is a positive correlation between job crafting and job satisfaction, (2) job satisfaction is clearly tied to organizational commitment, and (3) there is a negative link between job satisfaction and turnover intention, and finally, (4) organizational commitment is negatively related to turnover intention. These findings indicate that turnover intention may reduce by authorizing employees to bring on job crafting behavior, which ultimately will lead to employee satisfaction and commitment.